Effects of new assembled titanium mesh cage on the improvement in biomechanical performance of single-level anterior cervical corpectomy and fusion: a finite element analysis - Ke-rui Zhang; Yi Yang; Ya-qin Li; Li-tai Ma; Bei-yu Wang; Chen Ding; Yang Meng; Xin Rong; Ying Hong; Hao Liu (BMC Musculoskeletal Disorders)
Abstract Background Anterior cervical corpectomy and fusion (ACCF) with Traditional Titanium Mesh Cages (TTMCs) can lead to complications such as cage subsidence, dysphagia, and implant-related issues. These complications suggest that the biomechanical stability of ACCF with TTMC may be insufficient. This study aims to evaluate whether a New Assembled Titanium Mesh Cage (NTMC) can improve the biomechanical performance after ACCF. Methods ACCF procedures using both TTMC and NTMC models were constructed and compared. The range of motion (ROM) of the surgical segments and stress peaks in various regions including the endplate, bone-screw interface, facet joints, and adjacent intervertebral discs were analyzed. Results The use of NTMC significantly reduced the postoperative ROM of the surgical segments by 80.7%-82.0% compared to ACCF with TTMC. Additionally, stress peaks at the endplate, bone-screw interface, and facet contact force (FCF) were higher in ACCF with TTMC compared to NTMC. TTMC also induced higher stress peaks in the C3/4 and C6/7 intervertebral discs (ranging from 0.2009–6.961 MPa and 0.2477–4.735 MPa, respectively), followed by the NTMC (ranging from 0.1322–3.820 MPa and 0.2227–4.104 MPa, respectively). Conclusions The utilization of NTMC, which includes enlarged spacers and emulates endplate geometries, effectively reduces the risks of cage subsidence and instrument-related complications in ACCF. Furthermore, ACCF with NTMC also decreases the risks of dysphagia, facet joint degeneration, and adjacent disc degeneration during the follow-up period by altering the fixing method while maintaining construct stability.